Två somrar i Norra Ishafvet : kung Karls Land, Spetsbergens kringsegling, spanande efter Andrée, i nordöstra Grönland - Nathorst, A. G. (Alfred Gabriel), 1850-1921. (Stockholm : Beijer, 1900)
Includes index. Accounts of Swedish Arctic Expedition, 1898, and Swedish Expedition to East Greenland, 1899, both led by author. Mode of access: Internet.